Realignment of the ventricular septum in tetralogy of Fallot using (partial) direct closure of the ventricular septal defect: Long-term follow-up and comparison to conventional patch repair - Alexander Auer; Alessia Callegari; Vanessa Sitte; Rene Pretre; Hitendu Dave; Martin Christmann (Wolters Kluwer Medknow Publications, 2023)
Objectives : Aortic dilatation and regurgitation after surgical repair of tetralogy of Fallot (TOF) is known, and beside other factors, mainly addressed to an intrinsic aortopathy. In 2011, we reported the influence of realingement of the left ventricular outflow tract (LVOT) by (partial) direct closure of the ventricular septal defect (VSD) in TOF on aortic structures and function. We now evaluated the further follow-up of this cohort and compared the results to a matched group of TOF patients with classical VSD patch closure. Patients and Methods : Forty patients with TOF treated between 2003 and 2008 are included in the study, with 20 patients each in the VSD (a) (partial) direct closure and (b) patch closure group. Follow-up time after surgery was 12.3 years (11.3-13.0). Results : Patient characteristics, echocardiographic measurements, and surgical and intensive care unit parameters were not significantly different between both groups. After surgery and during long-term follow-up, realignement of the LVOT, shown by the angle between the interventricular septum and the anterior aortic annulus in long axis view in echocardiography, was lower in Group A (34 vs. 45°, P < 0.0001). No differences in LVOT or aortic annulus size, aortic regurgitation, or dilation of the ascending aorta and right ventricular outflow tract gradients were found. Transient rhythm disturbances were found in 3 patients in each group, with only one persistent complete atrioventricular block in Group B. Conclusion : (Partial) direct closure of the VSD in TOF leads to a better realignement of the LVOT and showed comparable short- and long-term results without higher risk for rhythm disturbances during follow-up.